Genomic profiling of gynecologic cancers and implications for clinical practice. Issue 1 (February 2017) - Prendergast, Emily N.; Elvin, Julia A.
Abstract : Purpose of review: This article summarizes advances in the application of next-generation sequencing (NGS) to the personalized treatment of gynecologic malignancies. Recent findings: Many recurrent genomic alterations (GA) in gynecologic malignancies have been identified by studies applying NGS to tumor tissue, which can provide insights into tumor biology, diagnostic or prognostic information, and potential targeted therapy options. NGS can be used to assay single genes, portions of multiple genes ("hot-spot" panels), or the complete coding sequence of a broad range of cancer-associated genes [i.e. comprehensive genomic profiling (CGP)]. CGP of a patient's tumor reveals to practitioners clinically relevant GA (CRGA) and associated biomarker-matched treatments, with a goal of improving therapeutic response while limiting cumulative chemotherapeutic toxicities. Although the use of precision medicine for gynecologic cancers holds much promise, the data detailing impact on survival and quality of life is still accumulating, lagging behind other areas of oncology. Enrolling gynecologic oncology patients in genotype-matched trials remains challenging and highlights the need for more molecular-based basket trials for reproductive tract malignancies. Summary: Identification of molecular subsets with distinct clinical attributes, prognostic significance, and targeted therapy directed options is now feasible in clinical gynecologic oncology practice.